Transport of Maxwell Fluid in a Cylindrical Tube Under the Influence of Wave Amplitude - Shukla V.K.; Chandra S.; Singh P.; Kumari B.; Kumar S. (My University, 2025)
In this article, we investigate the flow of a Maxwell fluid induced by peristaltic waves with progressively dilating wave amplitude and examine its impact on the swallowing of a single food bolus through the oesophagus. The effect of distinct parameters on the pressure is studied under the theory of long wavelength and low Reynolds number approximations. And it is concluded that the pressure, wall shear stress and reflux increses with increasing dilation parameter. © 2024 American Institute of Physics Inc.. All rights reserved.